Tuberculous meningitis: more questions, still too few answers. - Thwaites, G; van Toorn, R; Schoeman, J (2013)
Tuberculous meningitis is especially common in young children and people with untreated HIV infection, and it kills or disables roughly half of everyone affected. Childhood disease can be prevented by vaccination and by giving prophylactic isoniazid to children exposed to infectious adults, although improvements in worldwide tuberculosis control would lead to more effective prevention. Diagnosis is difficult because clinical features are non-specific and laboratory tests are insensitive, and treatment delay is the strongest risk factor for death. Large doses of rifampicin and fluoroquinolones might improve outcome, and the beneficial effect of adjunctive corticosteroids on survival might be augmented by aspirin and could be predicted by screening for a polymorphism in LTA4H, which encodes an enzyme involved in eicosanoid synthesis. However, these advances are insufficient in the face of drug-resistant tuberculosis and HIV co-infection. Many questions remain about the best approaches to prevent, diagnose, and treat tuberculous meningitis, and there are still too few answers.